The effects of local and landscape context on leafhopper (Hemiptera: cicadellinae) communities in coffeee agroforestry system of Costa Rica - Ramos, Mariangie (2008)
Tesis (Ph. D.) -- CATIE, Turrialba (Costa Rica) -- University of Idaho (Estados Unidos de América), 2008